Effect of two different UVA doses on the rabbit cornea and lens - Cejka, Cestmír; Pláteník, Jan; Buchal, Richard; Guryca, Vilém; Sirc, Jakub; Vejrazka, Martin; Crkovská, Jirina; Ardan, Taras; Michálek, Jirí; Brůnová, Blanka; Cejková, Jitka (Photochemistry and photobiology, 2009)
The aim of the present paper was to examine the irradiation effect of two doses of UVA rays (365 nm) on the rabbit cornea and lens. Corneas of anesthetized adult albino rabbits were irradiated with UVA rays for 5 days (daily dose 1.01 J cm(-2) in one group of rabbits and daily dose 2.02 J cm(-2) in the second group of animals). The third day after the last irradiation, the rabbits were killed, and their eyes were employed for spectrophotometrical, biochemical and immunohistochemical investigations. Normal eyes served as controls. Absorption spectra of the whole corneal centers were recorded over the UV-VIS (visible) spectral range. Levels of antioxidant and prooxidant enzymes, nitric oxide synthases and nitric oxide (indirectly measured as nitrate concentration) were investigated in the cornea. Malondialdehyde, a byproduct of lipid peroxidation, was examined in the cornea and lens. The results show that the staining for endothelial nitric oxide synthase was more pronounced in corneas irradiated with the higher UVA dose. Otherwise, UVA rays at either dose did not significantly change corneal light absorption properties and did not cause statistically significant metabolic changes in the cornea or lens. In conclusion, UVA rays at the employed doses did not evoke harmful effects in the cornea or lens.
Keywords: králíci; Lens, Crystalline; Rabbits; Ultraviolet Rays; ultrafialové záření; vztah dávky záření a odpovědi; oční čočka; Animals; Dose-Response Relationship, Radiation; rohovka; Cornea; zvířata